Ibuprofen compromises sexual behavior and fertility in female rats exposed during the perinatal period - Jorge, Bárbara Campos [UNESP]; Balin, Paola da Silva [UNESP]; Carneiro, Giovanna de Brito [UNESP]; Belleti, Rafael [UNESP]; Reis, Ana Carolina Casali [UNESP]; Stein, Julia [UNESP]; de Barros, Aline Lima; Kassuya, Cândida Aparecida Leite; Arena, Arielle Cristina [UNESP] (Taylor & Francis, 2020)
The influence of ibuprofen exposure during the perinatal period, when the brain sexual differentiation process occurs, on the sexual behavior and fertility of female offspring Wistar rats has been evaluated. Ibuprofen was orally administered to the dams at doses of 0, 10, 30 or 60 mg/kg during the gestational (from day 15 to delivery) and lactational period. Females exposed to ibuprofen showed no signs of maternal toxicity. However, ibuprofen provoked a reduction in intrauterine and postnatal growth in female offspring. The treated offspring also showed a decrease in the anogenital distance at birth, while no difference was observed in external signs of the onset of puberty. At adulthood, although the ibuprofen did not interfere with the estrous cyclicity, the lordosis quotient of treated females was reduced. Furthermore, these females presented reduced fertility and low fetal and placenta weights. The females also presented an increase in the percentage of small fetuses and a reduction in the large fetuses for their gestational ages. Perinatal exposure to ibuprofen may interfere with the sexual differentiation of the brain of female offspring of Wistar rats, causing a long-term impact in the sexual behavior and fertility of these females.
Keywords: female brain sexual differentiation; fertility; lordosis; pregnancy; Prostaglandins